Вклад бабстонов в ограничение информативности открытых линий связи между подводными объектами энергетики - Мышкин В. Ф. Вячеслав Фёдорович; Хан В. А. Валерий Алексеевич; Бурдакина О. В.; Семенов Д. А.; Усков Т. И.; Туголуков В. А. (2024, 2024)
Текстовый файл